Heterostructured Ti3C2Tx/carbon nanohorn-based gas sensor for NH3 detection at room temperature - Han, Yutong; Ding, Yuan; Yao, Yu; Li, Zhanhong; Zhu, Zhigang (Frontiers in Materials, 2024)
Herein, a two-dimensional Ti3C2Tx MXene compounded with the carbon nanohorn (CNH) by an electrostatic self-assembly method was proposed and then fabricated room temperature ammonia (NH3) gas sensors. The successful preparation of Ti3C2Tx/CNH nanocomposite has been detailed characterized. The NH3 sensing performance based on Ti3C2Tx/CNH also has been tested at room temperature. The optimal Ti3C2Tx/CNH sensor has a response of 21.6% to 100 ppm NH3 at room temperature, which is 10 times higher than that of the pure Ti3C2Tx sensor. Further, this sensor is endowed with an excellent selectivity, reliable long-term stability, and reproducibility. The enhanced sensing performance is associated with the interconnected structure and the synergistic effect of the Ti3C2Tx and CNH. This work provides an effective way to prepare MXene based sensitive materials for NH3 sensors, showing excellent NH3 detection potential at room temperature.